2018
DOI: 10.1038/s41598-018-34923-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, treatment and control of hypertension among hypertensive patients aged 18 to 59 years old in the northeast of China

Abstract: Hypertension not only has a high prevalence, but also brings disease burden to the affected patients. To assess the level of awareness, treatment and control of hypertension in the northeast of China, we investigated the rates of awareness, treatment and control of hypertension and identified its related factors among hypertensive patients aged 18 to 59 years old in Jilin, China. The data (n = 4632) for the present study were extracted from a cross-sectional study in Jilin. Among individuals with hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
6
5
0
Order By: Relevance
“…In agreement with the current study ndings, Zhang indicated that better disease control was inversely related to high cholesterol level (35). In addition, the present study ndings revealed that the individuals who drank alcohol had lower awareness about their status, which was in line with the results obtained by Lv et al (36).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the current study ndings, Zhang indicated that better disease control was inversely related to high cholesterol level (35). In addition, the present study ndings revealed that the individuals who drank alcohol had lower awareness about their status, which was in line with the results obtained by Lv et al (36).…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that age is a risk factor for coronary vascular diseases (CVD). However, in a study by Xin Lv et al [19] the level of awareness and attachment to the treatment of AH was significantly lower in young patients than in middle-aged patients (without statistical difference), but significantly lower than in older patients (p < 0.05). This can be explained by lifestyle and habits, frivolous perception of the disease, active social life, timeless for their own health, etc.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, it was noted that 54 % of patients learned about their high BP only when complications associated with AH appeared. Educational work, information policy and promotion of the annual medical examination should become a priority in the primary prevention of hypertension [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our research also relates to the literature on undiagnosed hypertension. Scholars in epidemiology have extensively studied the scope of undiagnosed hypertension in a wide array of countries including the United States (Foti et al, 2019;Johnston et al, 2009), Canada (Leung et al, 2020), France (Fenech et al, 2020), Australia, Finland, Germany, Ireland, Italy, Japan, New Zealand, South Korea, Spain and the United Kingdom (NCD-RisC, 2019) but also South Africa (Thomas et al, 2018), India (Anchala et al, 2014;Prenissl et al, 2019) and China (Lv et al, 2018). They emphasise the importance of age, obesity, but also education and income as factors associated with undiagnosed hypertension.…”
Section: Previous Research and Contributionmentioning
confidence: 99%